Expectant Versus Interventionist Care in the Management of Severe Preeclampsia Remote from Term: A Systematic Review - María Andrea Quintero-Ortíz; Carlos Fernando Grillo-Ardila; Jairo Amaya-Guio (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Objective To compare the effects of expectant versus interventionist care in the management of pregnant women with severe preeclampsia remote from term. Data sources An electronic search was conducted in the Medical Literature Analysis and Retrieval System Online (MEDLINE), Excerpta Medica Database (EMBASE), Cochrane Central Register of Controlled Trials (CENTRAL), Latin American and Caribbean Health Sciences Literature (LILACS, for its Spanish acronym), World Health Organization's International Clinical Trials Registry Platform (WHO-ICTRP), and Open- Grey databases. The International Federation of Gynecology and Obstetrics (FIGO, for its French acronym), Royal College of Obstetricians and Gynaecologists (RCOG), American College of Obstetricians and Gynecologists (ACOG), and Colombian Journal of Obstetrics and Gynecology (CJOG) websites were searched for conference proceedings, without language restrictions, up to March 25, 2020. Selection of studies Randomized clinical trials (RCTs), and non-randomized controlled studies (NRSs) were included. The Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approach was used to evaluate the quality of the evidence. Data collection Studies were independently assessed for inclusion criteria, data extraction, and risk of bias. Disagreements were resolved by consensus. Data synthesis Four RCTs and six NRS were included. Low-quality evidence from the RCTs showed that expectant care may result in a lower incidence of appearance, pulse, grimace, activity, and respiration (Apgar) scores<7 at 5 minutes (risk ratio [RR]: 0.48; 95% confidence interval [95%CI]: 0.23%to 0.99) and a higher average birth weight (mean difference [MD]: 254.7 g; 95%CI: 98.5 g to 410.9 g). Very low quality evidence from the NRSs suggested that expectant care might decrease the rates of neonatal death (RR: 0.42; 95%CI 0.22 to 0.80), hyalinemembrane disease (RR: 0.59; 95%CI: 0.40 to 0.87), and admission to neonatal care (RR: 0.73; 95%CI: 0.54 to 0.99). Nomaternal or fetal differences were found for other perinatal outcomes. Conclusion Compared with interventionist management, expectant care may improve neonatal outcomes without increasing maternal morbidity and mortality.